2014
DOI: 10.1016/j.eij.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A novel Neuro-fuzzy classification technique for data mining

Abstract: In our study, we proposed a novel Neuro-fuzzy classification technique for data mining. The inputs to the Neuro-fuzzy classification system were fuzzified by applying generalized bellshaped membership function. The proposed method utilized a fuzzification matrix in which the input patterns were associated with a degree of membership to different classes. Based on the value of degree of membership a pattern would be attributed to a specific category or class. We applied our method to ten benchmark data sets fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 17 publications
0
30
0
2
Order By: Relevance
“…Ghosh et al [17] studied about a new Neuro-fuzzy classification approach used for data mining. The data provided to the Neuro-fuzzy system underwent Fuzzification by using the generalized bell-structured membership function.…”
Section: Pramoda Patro Krishna Kumar G Suresh Kumarmentioning
confidence: 99%
“…Ghosh et al [17] studied about a new Neuro-fuzzy classification approach used for data mining. The data provided to the Neuro-fuzzy system underwent Fuzzification by using the generalized bell-structured membership function.…”
Section: Pramoda Patro Krishna Kumar G Suresh Kumarmentioning
confidence: 99%
“…The experimental results of their analysis classification techniques for mining showed that their approach improved identical dissemination of instances in ICDDR,B Hospital Surveillance data. each class Ghosh et al (2014). A novel Neuro-fuzzy Used a neuro-fuzzy data mining approach for classification of generalized bellclassification technique for data mining shaped membership functions.…”
Section: Malware Detection Based On Api Call Graphmentioning
confidence: 99%
“…A variety of system structures and learning algorithms are available for neuro-fuzzy methods [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Learning of the classical neuro-fuzzy systems is based on the gradient descent method [9].…”
Section: Introductionmentioning
confidence: 99%
“…An adaptive neuro-fuzzy system for building and optimizing fuzzy models has been proposed [14]. A variety of neuro-fuzzy methods are also proposed recently [15][16][17][18][19][20][21]. The applications of neurofuzzy methods include feature selection [19,21], classification [15][16][17][18][19][20], and image processing [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation